Ali Amini and his political role in Iran from 1961 to 1962 (Journal of the College of Basic Education, 2023)
This study gives us an overview of the political life of (Ali Amini), one of the political figures associated with the colonial powers in Iran since the beginning of his political life, and he was trying to direct Iran towards the United States and Britain, and the American government pressured Muhammad Reza Pahlavi to appoint Ali Amini as prime minister And with full powers, and that the American pressure was a threat to the Shah in 1961, he was told that if he did not agree to the demands of the new American administration, he would face the fall of his monarchy and presidential system, as General de Gaulle, the Chancellor of Germany and the Chancellor of the United Kingdom, said, despite the American views that seek to support the monarchy in Iran.